3D-QSAR and Docking Studies of a Series of β-Carboline Derivatives as Antitumor Agents of PLK1 - Jahan B. Ghasemi; Valentin Davoudian (Journal of Chemistry)
An alignment-free, three dimensional quantitative structure-activity relationship (3D-QSAR) analysis has been performed on a series of β-carboline derivatives as potent antitumor agents toward HepG2 human tumor cell lines. A highly descriptive and predictive 3D-QSAR model was obtained through the calculation of alignment-independent descriptors (GRIND descriptors) using ALMOND software. For a training set of 30 compounds, PLS analyses result in a three-component model which displays a squared correlation coefficient (r2) of 0.957 and a standard deviation of the error of calculation (SDEC) of 0.116. Validation of this model was performed using leave-one-out, q2loo of 0.85, and leave-multiple-out. This model gives a remarkably high r2pred(0.66) for a test set of 10 compounds. Docking studies were performed to investigate the mode of interaction between β-carboline derivatives and the active site of the most probable anticancer receptor, polo-like kinase protein.